2017
DOI: 10.4238/gmr16039742
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Synergic effect of oral contraceptives, GSTP1 polymorphisms, and high-risk HPV infection in development of cervical lesions.

Abstract: ABSTRACT. Human papillomavirus (HPV) infection is considered a risk factor for cervical cancer. Even if the high-risk HPV (HR-HPV) infection is necessary, environmental co-factors and genetic susceptibility also play an important role in cervical cancer development. In this study, a possible association of rs1695 GSTP1 polymorphisms, HR-HPV infection, and oral contraceptive use with cancer lesion development in women was investigated. The study population comprised 441 Brazilian women from the Northeast region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(38 reference statements)
0
5
0
1
Order By: Relevance
“…Our findings agreed with reports in the literature that progesterone hormones increase viral mRNA and significantly stimulate viral replication [ 39 , 64 , 65 ]. Studies on the relationship between contraceptive use and HPV infections have produced discordant findings in humans [ 27 , 55 , 66 , 67 ]. A recent study showed that contraceptives did not increase the risk of acquiring new HPV infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings agreed with reports in the literature that progesterone hormones increase viral mRNA and significantly stimulate viral replication [ 39 , 64 , 65 ]. Studies on the relationship between contraceptive use and HPV infections have produced discordant findings in humans [ 27 , 55 , 66 , 67 ]. A recent study showed that contraceptives did not increase the risk of acquiring new HPV infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the continuous stimulatory effect of the hormones on expression of the papillomavirus genes could also lead to an increase in expression of the viral oncogenes, i.e., E6 and E7, thereby enhancing their transforming potential. Nevertheless, most studies agree that a longer duration of contraceptive use (>5 years) can be a risk for viral persistence, a key factor for cancer development [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution profile of the GSTP1 A>G (rs1695) polymorphism varies according to the population, with the MAF (allele G ) ranging from 24.7% to 43% in the Brazilian population [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. As far as we know, there is no data on GSTP1 polymorphism frequency from other indigenous Brazilian populations focusing on mercury exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is estimated that around 291 million women carry HPV DNA, of whom 32% are infected with HPV16 or HPV18, or both 11 . Sexually transmitted infection 12 , hormonal contraceptives 5 , smoking 13 , early sexual intercourse 14 , multiple sexual partners 15 , high parity 16 , early pregnancy 17 are the risk factors associated with HPV supported by highly suggestive evidence.…”
Section: Introductionmentioning
confidence: 97%
“…Human papillomaviruses (HPV) are small double-stranded, unenveloped DNA viruses that infect the stratified epithelium 1 . HPV is the central risk factor for developing cervical cancer and is the third most common cancer in women 2 4 .HPV is the most common viral infection of the reproductive tract and it is estimated that approximately 98% of this disease is associated with oncogenic types of HPV 5 . There are more than 200 HPV genotypes present; among the major HRHPV genotypes are HPV16, 18, 31, 33,35, 39, 45, 51, 52, 56, 58, 59, 66 and 68 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%